Answer:
Your first step in solving the system would be to substitute the value of a variable into one of the equations
Step-by-step explanation:
We know that x = 2y + 2 and y = -1/3x + 4, so we could insert one of these values as the variable in one of the equations
If we were to insert -1/3x + 4 for y, our new equation would be:
x = 2(-1/3x + 4) + 2 (as you can see, the value of y was inserted into the equation)
Answer:
-3
Step-by-step explanation:
this is x equals to -3
we can divide the 4 to other side
Answer:
9 shirts
Step-by-step explanation:
12 - 6 = 6
6/2 = 3
3 times 3 = 9
Answer:
19
Step-by-step explanation: